Additive manufacturing of shape memory thermoset composites with directional thermal conductivity - Hong,Y; Azcune,I; Rekondo,A; Jiang,T; Zhou,S; Lowe,T; Saiz,E (Advanced Functional Materials, 2024)
Shape memory epoxy vitrimers and their composites are candidate materials for multiple engineering applications due to the commercial availability of their precursors combined with their functionality, mechanical properties, and recyclability. However, the manufacturing of vitrimer composites through conventional mould-casting limits the flexibility in the design of complex parts. In this work feedstock inks are formulated based on reduced graphene oxide and hexagonal boron nitride (hBN) to 3D-print epoxy vitrimer-based composites by direct ink writing (DIW). The introduction of hBN platelets (up to 22 vol.%) and their alignment during printing enhances the fracture resistance of the material and induces directional thermal transport. The in-plane thermal conductivities (3 W m−1 K−1) are nearly one order of magnitude higher than the matrix material. The high conductivity results in faster actuation times and can be combined with the printing process to build structures designed to manage heat flow.